Thank You, Reviewers of Acta Médica Portuguesa - Rui Tato Marinho; José Manuel Silva (Acta Médica Portuguesa, 2015)
Acta Médica Portuguesa is the only indexed Portuguese medical journal with a general scope, an audience of approximately 45,000 Portuguese doctors, other health professionals, reaching out to the general population. As such, the contribution of experts in several areas is crucial, supporting and identifying the most relevant issues, commenting on the relevance of the proposed studies and emphasizing innovative lines of the presented methodologies, amongst others.